WHAT MAKES AN ATTRACTIVE USER-FRIENDLY STREET? EXPLORING PERCEPTIONS OF MAWLAWI SHOPPING STREET ENVIRONMENT IN THE CONTEXT OF SULAYMANIYAH CITY, IRAQ - Khalaf, Omar Abdulwahhab; Ja`afar, Nor Haslina; Harun, Nor Zalina; Mohammed, Noraziah; Ali, Omar Hussein (PLANNING MALAYSIA, 2022)
Streets are one of the vital components of an urban form that supports the city dwellers’ public and private activities. Therefore, the purpose of attraction is necessary for persuading people to use the street and presenting the image of the city. Thus, the problem statement of this paper is that attractiveness of the shopping street decreases due to the presence of too much traffic management, and an uncomfortable environment attributed to an over-presence of traffic lights. Therefore, the objective of this paper is to determine the attraction factors associated with the user-friendliness of the shopping streets. This paper uses a case study approach of Mawlawi Street in Sulaymaniyah city in Iraq. The methodology used is the quantitative method via a survey of users (n = 330). The data were analysed statistically by SPSS using the mean values. The results show that the cultural attraction factor is the strongest form that contributes to people using the shopping street with a mean value of 3.1446. It is expected that the findings from this study will help designers, urban planners and policymakers to understand the needs and attitudes of users towards creating an attractive userfriendly shopping street environment in Iraq.